Human Rights as Ideology - García Belaunde, Domingo (1982)
This article examines the historical evolution of human rights and their current impact as a global phenomenon. It highlights that the global interest in human rights is not a creation of the United Nations (UN) alone, but rather a movement that has transcended local and regional boundaries. Although the UN has been instrumental in the promulgation of key documents such as the Universal Declaration of Human Rights and the The International Covenant on Economic, Social and Cultural Rights, its role in the promotion of human rights has been relatively limited. This is because the emergence of global interest in these rights responds more to a conjuncture driven by specific interests. In this context, the author analyzes the concept of ideology from two perspectives: the Marxist view, which sees ideology as a false consciousness that justifies class interests, and the analytical view, which sees it as a set of principles that justify political action. From this, he concludes that human rights cannot have an absolute rational foundation; rather, they are fluid and dependent on the values of each society and era, being used both to legitimize and to challenge political systems. Finally, the author underscores that human rights are a constantly evolving concept, shaped by social and political values, and their use in politics and ideology demonstrates versatility and importance in the struggle for power and the legitimization of regimes.